Are perfluorooctane sulfonate alternatives safer? New insights from a birth cohort study. (February 2020) - Chu, Chu; Zhou, Yang; Li, Qing-Qing; Bloom, Michael S.; Lin, Shao; Yu, Yun-Jiang; Chen, Da; Yu, Hong-Yao; Hu, Li-Wen; Yang, Bo-Yi; Zeng, Xiao-Wen; Dong, Guang-Hui
Highlights: Few human studies reported the associations of Cl-PFESAs exposure with birth outcomes. A birth cohort study was conducted in China to assess these associations. Cl-PFESAs was significantly associated with lower birth weight and preterm birth. The adverse effects of Cl-PFESAs on birth outcomes were similar with PFAS. PFOS alternatives (Cl-PFESAs) may be reproductive toxicants in human populations. Abstract: Background: Experimental studies show that chlorinated polyfluorinated ether sulfonic acids (Cl-PFESA 6:2 and 8:2), one of perfluoroalkyl substances (PFAS) used as perfluorooctane sulfonate (PFOS) alternatives, are reproductive toxicants in vivo and in vitro . However, the associations between gestational exposure to Cl-PFESAs and birth outcomes are unknown. Objectives: We investigated associations between 6:2 Cl-PFESA and 8:2 Cl-PFESA in maternal serum and birth outcomes. Methods: We measured four PFAS, including 6:2 Cl-PFESA, 8:2 Cl-PFESA, PFOS, and perfluorooctanoic acid (PFOA) in third-trimester maternal serum collected from 372 mother-child dyads participating in the Guangzhou Birth Cohort Study. Characteristics of mothers and infants were gathered from medical records and by interviewer-administered questionnaires. Results: PFOS was the most abundant PFAS in maternal serum (median: 7.15 ng/mL), followed by 6:2 Cl-PFESA (median: 2.41 ng/mL). Greater maternal serum levels of all PFAS alternatives were significantly associated with lower birth weight, adjusted for confounding variables. For example, each ln-ng/mL greater concentration of 6:2 Cl-PFESA and 8:2 Cl-PFESA was associated with a 54.44 g [95% confidence interval (CI): −95.66, −13.22] and 21.15 g (95% CI: −41.44, −0.86) lower birth weight, respectively. Greater continuous maternal serum 6:2 Cl-PFESA (OR: 2.67, 95% CI: 1.73, 4.15) and PFOS (OR: 2.03, 95% CI: 1.24, 3.32) were also associated with higher risks for preterm birth, adjusted for confounders, with a possible threshold effect at the highest quartile of 6:2 Cl-PFESA. Conclusions: For the first time, we report associations between maternal serum 6:2 Cl-PFESA and 8:2 Cl-PFESA concentrations and adverse birth outcomes. Our findings suggest that PFOS alternatives may be reproductive toxicants in human populations and should be considered with caution before widespread use. Given the preliminary nature of our results, additional epidemiological and toxicological investigations are needed to more definitively assess the risks.